Inguinal bladder hernia, a rare cause of inguinal herniation: Report of two cases - Aliou, Zabeirou Oudou; Somuah, Tenkorang; Anas, Belhaj; Alae Eddine, Aissaoui; Tarek, Souiki; Moulay Hassan, Farih; Karim, İbn Majdoub and Imane, Toughrai and Khalid, Mazaz (Journal of Surgery and Medicine, 2019)
Hernia surgery is the most frequent in visceral surgery. The bladder is rarely involved in groin hernia. This is when a diverticulum or a part of the bladder wall is incarcerated within the hernia. This affection is often asymptomatic. The diagnosis is made per-or post-operatively following complications. We report 2 cases of inguinal hernia involving the bladder in which the first case was diagnosed preoperatively whereas the second was diagnosed intraoperatively.